1966
DOI: 10.1080/00288233.1966.10429362
|View full text |Cite
|
Sign up to set email alerts
|

Boron deficiency in white clover (Trifolium repensL.) seedlings grown in an organic soil

Abstract: 1025In a pot trial using Rukuhia peat, white clover (Trifolium repells L.) seedlings grown without added boron developed distinctive deficiency symptoms. The addition of borax at 20 lb per acre increased the dry matter yield five-fold at the first harvest. This response diminished in subsequent harvests, and after three harvests there was no response in dry matter yield.BOro'l application increased the boron content of the plants at all harvests but it affected the nitrogen content of the plants in the same wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1969
1969
1990
1990

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The stems did not lengthen and a mass of stunted shoots developed at the base of the plant. These symptoms on young leaves are similar to those obtained in white clover seedlings (Sherrell 1966).…”
Section: B Deficiency Symptomssupporting
confidence: 72%
See 3 more Smart Citations
“…The stems did not lengthen and a mass of stunted shoots developed at the base of the plant. These symptoms on young leaves are similar to those obtained in white clover seedlings (Sherrell 1966).…”
Section: B Deficiency Symptomssupporting
confidence: 72%
“…However, there is such exact agreement for the critical range of B concentration in lucerne in this trial and those obtained in field trials and surveys (Sherrell & Toxopeus 1978;Sherrell 1983) that, by analogy, the data obtained here for clovers might also apply to the field.…”
Section: Critical Valuesmentioning
confidence: 73%
See 2 more Smart Citations
“…Unfortunately,criticalBconcentrations in clovers are not welldefined (Martin & Matocha 1973). With white clover, McNaught (1970) considered B concentrations below 25 J.l.g Big to indicate response but Sherrell (1966) reported no response whenplantconcentrations were12-20 J.l.g Big.Similarly,criticalBconcenttationsinredclovers are reported as ranging fromless than 12Ilg Big to 28 Ilg Big (Tucker & Smith 1952;Philipson 1953;Gupta 1984). Sherrell (1983a) suggested that the lack of agreement between different studies was caused by differences in environmental conditions under which theplants were grown.…”
Section: Resultsmentioning
confidence: 99%